2010
DOI: 10.1002/ajmg.b.31061
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in CAST are associated with Parkinson disease: A confirmation study

Abstract: Using data from the National Institutes of Neurological disease and Stroke's (NINDS) study of Parkinson disease (PD), we recently reported that single nucleotide polymorphisms (SNPs) in a region containing the Calpastatin (CAST) gene were associated with PD. Here we follow up this finding with an analysis of the Center for Inherited Disease Research's (CIDR) genome-wide association study in familial PD. After adjusting for population stratification and multiple testing, we find a significant association (p=0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This raises the question of whether single nucleotide polymorphisms (SNPs) in the CAST gene or regions that regulate mRNA expression for CAST may increase susceptibility for onset or severity of human IBD. In fact, 48 CAST SNPs have been identified, 20 within the CAST gene itself (39). None of these SNPs have to date been associated with either Crohn's disease or ulcerative colitis through genome-wide association studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of whether single nucleotide polymorphisms (SNPs) in the CAST gene or regions that regulate mRNA expression for CAST may increase susceptibility for onset or severity of human IBD. In fact, 48 CAST SNPs have been identified, 20 within the CAST gene itself (39). None of these SNPs have to date been associated with either Crohn's disease or ulcerative colitis through genome-wide association studies.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of data associating CAST SNPs with IBD is not surprising, given the complex genetic architecture of these diseases in humans (4). One disease that has been linked to CAST SNPs is Parkinson's Disease, which is a very different inflammatory disease (39, 40). In fact, the study of the calpain/CAST system in disease pathogenesis has to a large extent focused on its role in apoptosis related to ischemia/reperfusion injury, cancer, muscular dystrophy, or neurological disease (41).…”
Section: Discussionmentioning
confidence: 99%
“…PD prevalence was set at 0.02. Genotype relative risk was set according to the study of Allen et al [14]. Accordingly, the minimal sample size for cases or control was 464 (rs1065407) or less.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 5–10% of patients are now known to have monogenic forms of the disease [8] and recent genome-wide association studies (GWAS) identified several susceptibility loci albeit none of the results reached genome-wide significance [9][12]. Most recent studies pointed to a strong association between late-onset sporadic PD and two genetic variants (rs1559085 and rs27852) in calcium-dependent protease calpain inhibitor calpastatin (CAST) gene [13], [14]. These findings are of interest, because SN dopaminergic neurons have significant calcium-dependent pacemaker activity, and altered calcium homeostasis has been implicated PD pathogenesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Such strata are uninformative for association testing and lead to a decrease in power to detect SNP‐disease association. For this reason, in this article and in other publications, where we have used the stratification score to analyze GWAS data [Allen et al, ; Allen and Satten, , , ; Sarasua et al, ], we use principal components or spectral‐graph analysis (which produces ancestry components that are constructed without using information on disease) to construct Cj.…”
Section: Methodsmentioning
confidence: 99%